2011
DOI: 10.1103/physreva.83.062105
|View full text |Cite
|
Sign up to set email alerts
|

Testing quantum contextuality of continuous-variable states

Abstract: We investigate the violation of non-contextuality by a class of continuous variable states, including variations of entangled coherent states (ECS's) and a two-mode continuous superposition of coherent states. We generalise the Kochen-Specker (KS) inequality discussed in A. Cabello, Phys. Rev. Lett. 101, 210401 (2008) by using effective bidimensional observables implemented through physical operations acting on continuous variable states, in a way similar to an approach to the falsification of Bell-CHSH inequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…2 (b), we plot the optimal phase estimation as a function of N av , for the phase averaged states in Eqs. ( 13) and (15). We see that the enhancement of the optimal phase estimation is similar to the behavior shown in Fig.…”
Section: Generation Schemesupporting
confidence: 78%
See 1 more Smart Citation
“…2 (b), we plot the optimal phase estimation as a function of N av , for the phase averaged states in Eqs. ( 13) and (15). We see that the enhancement of the optimal phase estimation is similar to the behavior shown in Fig.…”
Section: Generation Schemesupporting
confidence: 78%
“…There are also probabilistic heralding schemes using photon subtraction or homodyne detections [11,12]. ECSs have a wide scope of applications ranging from fundamental tests of quantum mechanics [13][14][15][16] to practical quantum computation [17][18][19][20][21][22][23], communication [24][25][26], and metrology [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Schrödinger cat states, superpositions of two coherent states with coherent amplitudes of the same magnitude but different phases, have been widely studied for the significant role they could play in quantum information [1][2][3][4][5], computation [6,7] and in fundamental tests [8][9][10][11] as resource states. For example Ralph et al [3] showed that cat states can be used to implement qubit gates in an all optical quantum computation scheme, where the logical qubits are encoded in the phase of the coherent state complex amplitude and Jeong [8] considered the possibility of testing the Bell inequalities using cat-like states as resources.…”
Section: Introductionmentioning
confidence: 99%
“…Coherent state superpositions, or optical Schrödinger cat states, are widely recognized as promising resources in quantum information [1][2][3][4][5], quantum metrology [6][7][8], and fundamental tests [9][10][11][12]. In the near-orthogonal basis of coherent states γ|−γ = e −2γ 2 , two particular instances for these states are…”
mentioning
confidence: 99%